Synthesis and Electrochemical Properties of Two Transition Metal Coordination Complexes Based on 4-Pyridyl-Substituted TTF Ligand. Issue 7 (2nd July 2016) - Xiao, Debao; Meng, Liran; Zhou, Guoquan; Liang, Yue; Wang, Zhiqiang; Xiao, Xunwen
Abstract : The synthesis, crystal structures, and electrochemical properties of two transition metal coordination complexes, Co(acac)2 (EDO-TTF-4-py)2 2CH3 CN1, and ZnBr2 (EDO-TTF-4-py)2 2, are reported, where acac = acetylacetonate and EDO-TTF-4-py, L1 (EDO-TTF = ethylenedioxotetrathiafulvalene; py = pyridine). In complex1, two N atoms fromL1 are coordinated in the trans configuration to the Co(II) ion of Co(acac)2 to form an octahedral Co complex. And in complex2, the Zn(II) atom is tetrahedral by two N atoms fromL1 and two Br ions. Cyclic voltammetry measurements for both complexes show a sizable interaction involving the electroactiveL1 ligand and the metal ion.